Antibiotic prophylaxis of postoperative endophthalmitis after cataract surgery: Results of the 2014 ASCRS member survey - Chang, David F; Braga-Mele, Rosa; Henderson, Bonnie An; Mamalis, Nick; Vasavada, Abhay (Journal of cataract and refractive surgery, 2015)
A 2014 online survey of the American Society of Cataract and Refractive Surgery members indicated increasing use of intracameral antibiotic injection prophylaxis compared with a comparable survey from 2007. Forty-seven percent of respondents already used or planned to adopt this measure. One half of all surgeons not using intracameral prophylaxis expressed concern about the risks of noncommercially prepared antibiotic preparations. Overall, the large majority (75%) said they believe it is important to have a commercially available antibiotic approved for intracameral injection. Assuming reasonable cost, the survey indicates that commercial availability of Aprokam (cefuroxime) would increase the overall percentage of surgeons using intracameral antibiotic injection prophylaxis to nearly 84%. Although the majority used topical perioperative antibiotic prophylaxis, and gatifloxacin and moxifloxacin were still the most popular agents, there was a trend toward declining use of fourth-generation fluoroquinolones (60%, down from 81% in 2007) and greater use of topical ofloxacin and ciprofloxacin (21%, up from 9% in 2007).